Effects of musical expertise on line section and line extension - Pei, Yilai; Xu, Zhiyuan; He, Yibo; Liu, Xinxin; Bai, Yuxuan; Kwok, Sze Chai; Li, Xiaonuo; Wang, Zhaoxin (Frontiers in Psychology, 2024)
This study investigated whether music training led to better length estimation and/or rightward bias by comparing the performance of musicians (pianists) and nonmusicians on performance of line sections and line extensions. One hundred and sixteen participants, among them 62 musicians and 54 nonmusicians, participated in the present study. The mixed repeated measures ANOVA analysis revealed a significant group × condition interaction, that the musicians were more accurate than nonmusicians in all the line section tasks and showed no obvious pseudoneglect, while their overall performance on the line extension tasks was comparable to the non-musicians, and only performed more accurately in the 1/2 line extension condition. These findings indicated that there was a dissociation between the effects of music training on line section and line extension. This dissociation does not support the view that music training has a general beneficial effect on line estimation, and provides insight into a potentially important limit on the effects of music training on spatial cognition.